Edukasi Dan Pendapingan Digital Di Masa Pandemi Covid-19 Bagi Usaha Mikro Di Desa Kuwik Kecamatan Kunjang Kabupaten Kediri - Fita Binti Nurjanah; Fadhil Akbar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
A type of virus from the family Coronaviridae that causes infectious and deadly diseases that attack mammals such as humans in the respiratory tract to the lungs. In the beginning of people with corona virus or Covid-19 will experience early symptoms in the form of fever, sore throat, cold and also coughing even to severe can cause pneumonia. This virus can be transmitted through direct contact in close proximity with people with coronavirus or Covid-19 through respiratory fluids that come out of the patient's body when coughing or removing saliva and riyak. That's why the Government of Indonesia is currently increasing social distancing activities. Where residents are asked to always keep a distance of 1-2 meters when interacting with the surrounding community to avoid the spread of coronavirus or Covid-19. As a result, schools, universities, agencies that are still under the auspices of the government are closed operational activities during the coronavirus pandemic or Covid-19 and replaced with activities at home only or the new term is work from home. Indirectly this will result in a weakening of the economy. The markets are quiet, small traders are also quiet because many people do activities at home. Companies and also Micro, Small and Medium Enterprises will experience inevitable losses due to the Corona Virus or Covid-19 pandemic because the products marketed are quiet buyers. However, in this digital and modern era, companies and micro traders can start utilizing the internet / virtual world as a substitute for the market. Companies and also Micro, Small and Medium Enterprises can take advantage of social media applications that are now being loved by the public such as WhatsApp, Facebook and other social media as a market to offer their products. And here we will also explain how to offer our products using the marketplace feature on social media. where between sellers and buyers do not meet each other but sellers can market through the phone or social media so that consumers can know the goods sold and ordered by telephon, without having to come to each other only at home only goods ordered between to the house so as to minimize the risk of spreading the corona virus or Covid-19 and the economic wheels in the village of Kuwik and surrounding areas can run in the middle of the coronavirus pandemic or Covid-19.